Menyiapkan SDM Unggul dan Religius melalui Ikhtiar Kegiatan Keagamaan di Desa Jonjo Kabupaten Gowa - Askar Patahuddin; Jujuri Perdamaian Dunia (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
Creating superior and religious human resources is a provision for realizing civil society. The aim of this community service is to prepare superior and religious human resources in Jonjo village through various religious programs in the village. Community service was carried out by ten STIBA Makassar students. Efforts to create a superior and religious Jonjo village community through activities of 1) dirosa; 2) teaching tahsin; 3) teaching TKA / TPA; 4) sunset and dawn rituals; 5) khutbah jum'at; 6) training for organizing the body; 7) pious children festival; 8) tabligh akbar. In general, the student KKN activities of the 3rd batch of STIBA Makassar students in Jonjo Village went well and smoothly. All work programs implemented have been welcomed and enthusiastically by the government and society. The obstacle that becomes a challenge in the process of implementing work programs is that the majority of community activities work as farmers in rice fields, making students need to manage the time for carrying out more activities at night so that the community can be more fully involved.